1997
DOI: 10.1515/znc-1997-9-1016
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics from Brazilian Propolis

Abstract: The main phenolic constituents from Brazilian propolis, originating from Sao Paulo State, were isolated and identified: three flavonoids, a prenylated coumaric acid and two new benzopyranes, E and Z 2,2-dimethyl-6-carboxyethenyl-8-prenyl-2H-benzopyranes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 11 publications
4
34
0
5
Order By: Relevance
“…Myricetin 3,7,4',5'-tetramethyl 11 ether and quercetin 3,7,3'-trimethyl ether 12 were isolated from Tunisian propolis, which originated from leaf exudates of Cistus species [34]. In Brazilian samples, kaempferid, 5,6,7-trihydroxy-3,4'-dihydroxyflavon 13, aromadendrine-4'methyl ether 14 [14] and 3,5,7-trihydroxy-6,4'-dimethoxyflavon 15 [9] were identified.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myricetin 3,7,4',5'-tetramethyl 11 ether and quercetin 3,7,3'-trimethyl ether 12 were isolated from Tunisian propolis, which originated from leaf exudates of Cistus species [34]. In Brazilian samples, kaempferid, 5,6,7-trihydroxy-3,4'-dihydroxyflavon 13, aromadendrine-4'methyl ether 14 [14] and 3,5,7-trihydroxy-6,4'-dimethoxyflavon 15 [9] were identified.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Another class of phenolics newly found in Brazilian bee-glue, are prenylated p-coumaric acids and their derivatives with cyclized prenyl residues: 16-22 [1,9,14,39,47].…”
Section: Prenylated P-coumaric Acids and Acetophenonesmentioning
confidence: 99%
“…Telefax: (+5514) 3811-7189, E-mail: orsi@fca.unesp.br compounds (flavonoids, aromatic acids, benzopyranes), di-and triterpenes, essential oils, among others. Seasonal variations in propolis composition are not significant and are predominantly quantitative (2,4,6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of our group revealed that propolis (100 mg/kg) decreased by 55% the cholesterol levels of hypercholesterolemia-induced rabbits (14). Free fatty acids were significantly decreased at the 21 st day in P10 group ( Figure 1 -B).…”
Section: Resultsmentioning
confidence: 58%